A cadmium sulfide composite material and its preparation method and application
By supporting polyethyleneimine-modified Ti3C2 quantum dots on the cadmium sulfide nanorods, forming composite materials, solving the problems of cadmium sulfide photocorrosion and instability of precious metal cocatalysts, significantly improving its photocatalytic activity and hydrogen evolution efficiency.
Patent Information
- Application Number
- CN202210024949.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-01-11
AI Technical Summary
Cadmium sulfide is prone to photocorrosion under light, causing photogenerating electrons and holes to recombine, reducing its photocatalytic activity. At the same time, the existing precious metal cocatalysts are unstable and expensive, limiting their application in photohydrogen production.
By loading polyethyleneimine-modified Ti3C2 quantum dots on the cadmium sulfide nanorods, a composite material is formed, and the strong interaction between the Ti3C2 quantum dots and the cadmium sulfide nanorods are used to improve the migration and separation efficiency of photogenerated electrons.
The stability and photocatalytic efficiency of the cadmium sulfide composite material are significantly improved, and the hydrogen evolution efficiency of photolysis of aquatic hydrogen under visible light is more than 5 times that of conventional cadmium sulfide nanorods supported by Pt as a cocatalyst.
Smart Images

Figure CN114534756B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic materials, and in particular relates to a cadmium sulfide composite material and a preparation method and application thereof. Background Art
[0002] The only product of hydrogen (H2) combustion is clean water, which can be regenerated from water. Therefore, hydrogen is considered an ideal clean energy. Since Honda and Fujishima pioneered the research precedent of converting solar energy into hydrogen energy, photocatalytic reduction and decomposition of water to produce hydrogen is expected to achieve green and sustainable development of energy. With the development of human society, the massive consumption of fossil energy and the increasingly serious energy crisis, the development of new energy has become an issue that humans have to consider. Solar energy is inexhaustible, and converting it into chemical energy that we can use has become a key research task for humans.
[0003] Cadmium sulfide (CdS) is an important semiconductor photocatalytic material, especially CdS nanorods, which have a narrow band gap (about 2.4eV), a suitable band gap position, a large aspect ratio and excellent charge transfer efficiency. However, its defect is that after CdS is excited by light, long-term illumination will cause CdS photocorrosion, and the generated photogenerated electrons and holes are easy to recombine, which reduces its photogenerated carrier efficiency and seriously restricts its photocatalytic activity. At the same time, the co-catalyst currently used in photocatalytic hydrogen production is often a precious metal such as platinum (platinum, Pt), which is expensive and unstable during the reaction process. These greatly limit the development of CdS photocatalytic water splitting to produce hydrogen. Therefore, finding a lower-priced co-catalyst and improving the photocatalytic stability of CdS have important theoretical significance and practical application value for the research of CdS with high photocatalytic activity. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a cadmium sulfide composite material, which has the characteristics of high stability, high electron-hole separation rate and high photocatalytic efficiency, and is applied to photolysis of water to produce hydrogen under visible light, and its hydrogen evolution efficiency is more than 5 times that of conventional cadmium sulfide nanorods loaded with Pt as a co-catalyst.
[0005] The invention also provides a method for preparing the cadmium sulfide composite material.
[0006] The invention also provides an application of the cadmium sulfide composite material.
[0007] A first aspect of the present invention provides a cadmium sulfide composite material, comprising cadmium sulfide nanorods and Ti3C2 quantum dots loaded on the cadmium sulfide nanorods.
[0008] A technical solution of the cadmium sulfide composite material of the present invention has at least the following beneficial effects:
[0009] The present invention introduces polyethyleneimine-modified Ti3C2 quantum dots into cadmium sulfide nanorods, so that the polyethyleneimine-modified Ti3C2 quantum dots are loaded on CdS nanorods. Since polyethyleneimine (PEI) is used to modify the Ti3C2 quantum dots, PEI is easily cross-linked and coupled with hydroxyl groups on the surface of the material, that is, there is a strong interaction between the Ti3C2 quantum dots and the cadmium sulfide nanorods, thereby forming a heterojunction, which is conducive to the rapid migration of photogenerated electrons and improves the photocatalytic performance of cadmium sulfide. The cadmium sulfide composite material has the characteristics of high stability, high electron-hole separation rate and high photocatalytic efficiency. It is applied to photolysis of water to produce hydrogen under visible light, and its hydrogen evolution efficiency is more than 5 times that of conventional cadmium sulfide nanorods loaded with Pt as a co-catalyst.
[0010] According to some embodiments of the present invention, the mass fraction of the polyethyleneimine-modified Ti3C2 quantum dots is 1-7% based on the total mass of the cadmium sulfide composite material. If the content of the quantum dots is too low, the carrier separation efficiency is not obvious. If the amount of the quantum dots used exceeds 7%, the CdS nanorods will be covered, resulting in a decrease in their optical absorption capacity and affecting the photocatalytic activity of the material. Therefore, the mass fraction of the polyethyleneimine-modified Ti3C2 quantum dots is 1-7%, which is the best effect.
[0011] According to some embodiments of the present invention, the diameter of the polyethyleneimine-modified Ti3C2 quantum dots is 3 to 10 nm.
[0012] According to some embodiments of the present invention, the cadmium sulfide nanorods have a diameter of 20 to 30 nm and a length of 1 to 1.5 μm.
[0013] A second aspect of the present invention provides a method for preparing a cadmium sulfide composite material, comprising the following steps:
[0014] S1: Dispersing cadmium sulfide nanorods and polyethyleneimine-modified Ti3C2 quantum dots in a solvent to obtain a suspension;
[0015] S2: freeze-drying the suspension.
[0016] According to some embodiments of the present invention, the synthesis method of the cadmium sulfide nanorods refers to the literature: JS Jang, UA Joshi, et al. J. Phys. Chem. C 111 (2007) 13280-13287.
[0017] According to some embodiments of the present invention, the synthesis method of the polyethyleneimine-modified Ti3C2 quantum dots refers to Li Y, Ding L, Guo Y, et al. Boosting the photocatalytic ability of g-C3N4 forhydrogen production by Ti3C2 MXene quantum dots. ACS applied materials&interfaces, 2019, 11(44): 41440-41447.
[0018] According to some embodiments of the present invention, the mass ratio of the cadmium sulfide nanorods to the polyethyleneimine-modified Ti3C2 quantum dots is 100:(1-7).
[0019] According to some embodiments of the present invention, in step S2, the freeze-drying temperature is -65°C to -55°C.
[0020] According to some embodiments of the present invention, in step S2, the freeze-drying pressure is 1-10 Pa.
[0021] According to some embodiments of the present invention, the preparation method further comprises grinding the product after freeze-drying.
[0022] The third aspect of the present invention provides the use of the above-mentioned cadmium sulfide composite material as a catalyst in photocatalytic water splitting to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A transmission electron microscope image of the cadmium sulfide composite material prepared in Example 2;
[0024] Figure 2 A high-resolution transmission electron micrograph of the cadmium sulfide composite material prepared in Example 2;
[0025] Figure 3 X-ray diffraction patterns of the cadmium sulfide composite materials prepared in Examples 1 to 5 of the present invention and Comparative Example 1;
[0026] Figure 4 The photoluminescence spectra of the cadmium sulfide composite materials prepared in Example 2 of the present invention and Comparative Example 1;
[0027] Figure 5 The impedance diagrams of the cadmium sulfide composite materials prepared in Examples 1 to 5 and Comparative Example 1 of the present invention;
[0028] Figure 6 This is a graph of the quantum yield of the cadmium sulfide composite material prepared in Example 2 of the present invention;
[0029] Figure 7 This is a stability diagram of the cadmium sulfide composite material prepared in Example 2 of the present invention;
[0030] Figure 8 This is a test chart of the efficiency of photodegradation of water and hydrogen evolution of the cadmium sulfide composite material prepared in Examples 1 to 5 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention will be described clearly and completely below, but the implementation manner of the present invention is not limited thereto.
[0032] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0033] The specific synthesis method of the cadmium sulfide nanorods described in this example is referred to JS Jang, UA Joshi, et al. J. Phys. Chem. C 111 (2007) 13280-13287.
[0034] The preparation method of polyethyleneimine-modified Ti3C2 quantum dots described in this embodiment refers to Li Y, Ding L, Guo Y, et al. Boosting the photocatalytic ability of g-C3N4 for hydrogen production by Ti3C2MXene quantum dots. ACS applied materials & interfaces, 2019, 11 (44): 41440-41447.
[0035] Example 1
[0036] Example 1 A cadmium sulfide composite material is prepared, the cadmium sulfide composite material includes cadmium sulfide nanorods and polyethyleneimine-modified Ti3C2 quantum dots supported on the cadmium sulfide nanorods; the CdS nanorods have a diameter of 20 to 30 nm and a length of 1 to 1.5 μm, and the polyethyleneimine-modified Ti3C2 quantum dots have a diameter of 5 nm. The preparation method thereof comprises the following steps:
[0037] S1. Weigh 40 mg of CdS nanorods and add 40 mL of water, sonicate, stir evenly, add 100 μL of 0.4 g / L polyethyleneimine-modified Ti3C2 quantum dots to obtain a suspension;
[0038] S2. The suspension was evaporated under freeze-drying conditions at -60°C and 8Pa pressure to obtain a yellow powder;
[0039] S3. Cool naturally to room temperature, grind the obtained sample again, and the obtained product is marked as CdS@100Ti3C2 QDs.
[0040] Example 2
[0041] Example 2 A cadmium sulfide composite material was prepared, the cadmium sulfide composite material comprising cadmium sulfide nanorods and polyethyleneimine-modified Ti3C2 quantum dots supported on the cadmium sulfide nanorods; the CdS nanorods had a diameter of 20 to 30 nm and a length of 1 to 1.5 μm, and the polyethyleneimine-modified Ti3C2 quantum dots had a diameter of 5 nm. The preparation method thereof comprised the following steps:
[0042] S1. Weigh 40 mg of CdS nanorods and add 40 mL of water, sonicate, stir evenly, add 200 μL of 0.4 g / L polyethyleneimine-modified Ti3C2 quantum dots to obtain a suspension;
[0043] S2. The suspension was evaporated under freeze-drying conditions at -60°C and 8Pa pressure to obtain a yellow powder;
[0044] S3. Cool naturally to room temperature, grind the obtained sample again, and the obtained product is marked as CdS@200Ti3C2 QDs.
[0045] Example 3
[0046] Example 3 A cadmium sulfide composite material was prepared, the cadmium sulfide composite material comprising cadmium sulfide nanorods and polyethyleneimine-modified Ti3C2 quantum dots supported on the cadmium sulfide nanorods; the CdS nanorods had a diameter of 20 to 30 nm and a length of 1 to 1.5 μm, and the polyethyleneimine-modified Ti3C2 quantum dots had a diameter of 5 nm. The preparation method thereof comprised the following steps:
[0047] S1. Weigh 40 mg of CdS nanorods and then add 40 mL of water, sonicate, stir evenly, add 300 μL of 0.4 g / L polyethyleneimine-modified Ti3C2 quantum dots to obtain a suspension;
[0048] S2. The suspension was evaporated under freeze-drying conditions at -60°C and 8Pa pressure to obtain a yellow powder;
[0049] S3. Cool naturally to room temperature, grind the obtained sample again, and the obtained product is marked as CdS@300Ti3C2 QDs.
[0050] Example 4
[0051] Example 4 A cadmium sulfide composite material was prepared, the cadmium sulfide composite material comprising cadmium sulfide nanorods and polyethyleneimine-modified Ti3C2 quantum dots supported on the cadmium sulfide nanorods; the CdS nanorods had a diameter of 20 to 30 nm and a length of 1 to 1.5 μm, and the polyethyleneimine-modified Ti3C2 quantum dots had a diameter of 5 nm. The preparation method thereof comprised the following steps:
[0052] S1. Weigh 40 mg of CdS nanorods and then add 40 mL of water, sonicate, stir evenly, add 500 μL of 0.4 g / L polyethyleneimine-modified Ti3C2 quantum dots to obtain a suspension;
[0053] S2. The suspension was evaporated under freeze-drying conditions at -60°C and 8Pa pressure to obtain a yellow powder;
[0054] S3. Cool naturally to room temperature, grind the obtained sample again, and the obtained product is marked as CdS@500Ti3C2 QDs.
[0055] Example 5
[0056] Example 5 A cadmium sulfide composite material was prepared, the cadmium sulfide composite material comprising cadmium sulfide nanorods and polyethyleneimine-modified Ti3C2 quantum dots supported on the cadmium sulfide nanorods; the CdS nanorods had a diameter of 20 to 30 nm and a length of 1 to 1.5 μm, and the polyethyleneimine-modified Ti3C2 quantum dots had a diameter of 5 nm. The preparation method thereof comprised the following steps:
[0057] S1. Weigh 40 mg of CdS nanorods and add 40 mL of water, sonicate, stir evenly, add 700 μL of 0.4 g / L polyethyleneimine-modified Ti3C2 quantum dots to obtain a suspension;
[0058] S2. The suspension was evaporated under freeze-drying conditions at -60°C and 8Pa pressure to obtain a yellow powder;
[0059] S3. Cool naturally to room temperature, grind the obtained sample again, and the obtained product is marked as CdS@700Ti3C2 QDs.
[0060] Comparative Example 1
[0061] The raw materials and preparation method of Comparative Example 1 are the same as those of Example 1, the only difference is that no polyethyleneimine-modified Ti3C2 quantum dots are added to S1 of Comparative Example 1, and the polyethyleneimine-modified Ti3C2 quantum dots are replaced by 3wt% Pt, a precious metal, and the obtained product is marked as CdS nanorods + Pt.
[0062] Test Example 1
[0063] Transmission electron microscope (TEM) morphology:
[0064] The transmission electron microscope (TEM) morphology of the sample obtained in Example 2 is as follows: Figure 1 As shown in the TEM image, it can be seen that the cadmium sulfide composite material presents a complete one-dimensional rod-like structure, and some fine particles, namely Ti3C2 quantum dots, are evenly dispersed on the surface of the nanorods. The full combination of the two promotes the rapid migration of photogenerated electrons, greatly improving the photocatalytic performance of the material.
[0065] Figure 2 The high-resolution transmission electron microscopy (TEM) image of the prepared cadmium sulfide composite material shows that the size of the Ti3C2 quantum dots is 3 to 10 nm.
[0066] Test Example 2
[0067] X-ray diffraction (XRD) test:
[0068] The X-ray diffraction (XRD) patterns of the samples obtained in Examples 1 to 5 and Comparative Example 1 are as follows: Figure 3 As shown. Figure 3 It can be seen that cadmium sulfide nanorods show a typical hexagonal phase structure. In addition, after the Ti3C2 quantum dots and cadmium sulfide nanorods were composited, the obtained samples CdS@xTi3C2 QDs all showed a hexagonal phase, which shows that the addition of Ti3C2 quantum dots did not interfere with the phase change of the material. During the composite process, the content of Ti3C2 quantum dots increased, and no obvious diffraction peak of Ti3C2 was found, indicating that its loading was low and its dispersion was high.
[0069] Test Example 3
[0070] Photoluminescence spectrum and impedance test:
[0071] The photoluminescence spectra of the samples CdS@200Ti3C2 QDs and CdS nanorods+Pt obtained in Example 2 and Comparative Example 1 are as follows: Figure 4 As shown. Figure 4 It can be seen that the fluorescence quenching of the sample CdS@200Ti3C2 QDs is more obvious than that of the sample CdS nanorods, which indicates that the appropriate amount of Ti3C2 quantum dots loaded on the CdS nanorods can inhibit the recombination of photogenerated electrons and photogenerated holes, thereby greatly improving the performance of the photocatalytic material. In addition, the impedance spectra of the samples obtained in Examples 1 to 5 and Comparative Example 1 are as follows Figure 5 As shown, compared with CdS nanorods + Pt, the impedance of the CdS@x Ti3C2 QDs composite material gradually decreases with the increase of Ti3C2 quantum dots, indicating that the electron migration resistance of the composite material is reduced.
[0072] Test Example 4
[0073] Quantum yield and stability test:
[0074] The quantum yield of the sample CdS@200Ti3C2 QDs obtained in Example 2 is as follows Figure 6 As shown. Figure 6 It can be seen that under a series of monochromatic illumination, the variation trend of the AQE value of CdS@200Ti3C2 QDs is in good agreement with the light absorption spectrum, indicating that the photocatalytic hydrogen evolution is mainly driven by the captured photons in the CdS@200Ti3C2 QDs system. At the same time, in order to detect the photocatalytic stability of CdS@200Ti3C2 QDs, 6 cycles of tests were also carried out, such as Figure 7 As shown, there is almost no obvious deactivation of CdS@200Ti3C2 QDs within 24 h.
[0075] Test Example 5
[0076] Photocatalytic water splitting hydrogen production efficiency test:
[0077] The cadmium sulfide composite materials prepared in Examples 1 to 5 and Comparative Example 1 have a photocatalytic water decomposition hydrogen production efficiency of Figure 8 As shown. Figure 8 It can be seen that under the condition of visible light illumination, the hydrogen production rates of the composite materials from CdS@100Ti3C2 QDs to CdS@700Ti3C2 QDs are 14.63mmol·g -1 ·h -1 , 16.53mmol·g -1 ·h -1 , 15.24mmol·g -1 ·h -1 , 14.83mmol·g -1 ·h -1 、12.92mmol·g -1 ·h -1 Compared with the photocatalytic hydrogen production efficiency of CdS nanorods (nonarod) + Pt in comparative example 1 (3.25mmol·g -1 ·h -1 ), the hydrogen production rate of the composite materials has been significantly improved.
[0078] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. Application of a cadmium sulfide composite material as a catalyst in photocatalytic water splitting to produce hydrogen, characterized in that: The cadmium sulfide composite material consists of cadmium sulfide nanorods and polyethyleneimine-modified Ti3C2 quantum dots loaded on the cadmium sulfide nanorods; Calculated based on the total mass of the cadmium sulfide composite material, the mass fraction of the polyethyleneimine-modified Ti3C2 quantum dots is 1-7%.
2. The use according to claim 1, characterized in that: The diameter of the polyethyleneimine-modified Ti3C2 quantum dots is 3-10 nm.
3. The use according to claim 1, characterized in that: The cadmium sulfide nanorods have a diameter of 20-30 nm and a length of 1-1.5 μm.
4. The use according to claim 1, characterized in that: The preparation method of the cadmium sulfide composite material comprises the following steps: S1: Dispersing cadmium sulfide nanorods and polyethyleneimine-modified Ti3C2 quantum dots in a solvent to obtain a suspension; S2: freeze-drying the suspension.
5. The use according to claim 4, characterized in that: In step S2, the freeze-drying temperature is -65°C to -55°C.
6. The use according to claim 4, characterized in that: In step S2, the freeze-drying pressure is 1-10 Pa.
7. The use according to claim 4, characterized in that: The preparation method further comprises grinding the product after freeze drying.
Citation Information
Patent Citations
One-dimensional cadmium sulfide / two-dimensional titanium carbide composite photocatalyst and preparation method and application thereof
CN110773213A